Perianal erosive papulonodular dermatosis secondary to surgery for Hirschsprung disease. - Hormi, O.; El yamani, L.; Moujahid, S.; Zerrouki, N.; Zizi, N. (European Journal of Pediatric Dermatology, 2025)
Hirschsprung’s disease is a congenital disorder characterized by the absence of ganglion cells in the distal colon, leading to functional obstruction. Surgical intervention is often required to alleviate symptoms. We present a rare case of erosive papulo-nodular perianal dermatitis mimicking condyloma as a postoperative complication of Hirschsprung’s disease in a 19-month-old boy. Although rare, awareness of this entity is crucial to avoid misdiagnosis and ensure appropriate management.